(untitled) (Journal of the College of Basic Education, 2023)
Oh God, we praise you for what you have taught of the statement. And inspired by the clarification. We also thank you for the gifts you have bestowed... May God bless our master Muhammad and his good and pure family and companions.As for after...Arabic rhetoric is one of the most enjoyable and beautiful arts, as it carries all the expressions with deep meaning from which the creator sets out to search for his own meanings contained within these expressions. Modern science has taken advantage of the aesthetic advantage that rhetoric enjoys to produce for us an art that stands on its own, which is persuasion, to be one of the skills. Human communication is human nature, and man by nature seeks to persuade the recipient towards his way of thinking, and the weapon with which a person who masters this art fights is strong knowledge of his audience, and he uses that knowledge to speak in their language, imitate their thoughts, and try to employ it in a way that serves his purpose and desire, as every communication process aims to persuade the sender in an enjoyable and interesting manner. The method is not the goal, but rather the method in communicating this goal, and here the role of eloquence is highlighted in communicating it through the use of a group of eloquent entertaining methods that attract the heart of the listener or reader before his mind. The importance of the study lies in our study of a book from the Arab heritage and its analysis according to modern study, and on this the research was centered. About (the levels of the persuasive roles of graphic methods in the book Al-Mawrid Al-Athb fi Sermons and Sermons by Ibn Al-Jawzi (d. 597 AH).), and my study will be in the following form, as I will start with metaphor because it represents an important center for persuasion and then simile, and finally I touched on metonymy and these methods All of them feed into the analysis of various samples from the book Al-Mawrid Al-Athb in Sermons and Sermons.